Pengaruh Luas Lubang Bukaan Dinding Terhadap Energi Disipasi Portal Beton Bertulang - Marsa, Raihan Jetson; Sunaryati, Jati; Tanjung, Jafril (Universitas Andalas, 2024)
Brick walls in portal structures are often considered non-structural components or parts of the architecture; consequently, the influence of the brick walls' strength and stiffness is often not considered in building planning. In reality, brick walls have a certain value of strength and stiffness in resisting lateral loads. In reinforced concrete buildings, the portal structure is filled with solid brick walls and brick walls with openings (holes) that serve as spaces for installing windows, doors, ventilation, and so on. This study aims to analyze the influence of the opening area on the lateral performance of reinforced concrete portals under cyclic loading. This study was conducted by comparing six specimen models, namely reinforced concrete portal structures with full walls (F-O-0), reinforced concrete portal structures with an opening area in the wall of 15% (F-O-15), 25% (F-O-25), 40% (F-O-40), 55% (F-O-55), and reinforced concrete portal structures without walls. (F-O-100). The research was conducted numerically using the ATENA V5.9.0 software (Demo Version). The outputs obtained with the help of the ATENA software that will be compared are the load-displacement hysteresis curves and the effect of the opening area on the wall. From the analysis results, it can be concluded that there is a decrease in energy dissipation as the opening area on the infill wall increases.